Entre orquídeas e girassóis :o laboratório de Enfermagem na visão de estudantes - Gomes, Cleide Oliveira (2004)
To study the teaching/learning process about the Nursing procedures carried out in the laboratory, and learn both the sapiens and the demens dimensions of such process, is the main purpose of this study. The objectives are to: identify the major laboratory contributions to the teaching/learning process from the point of view of undergraduate students and the feelings they express; describe the difficulties they have identified; and analyze the relevance of the laboratory to this process. As part of the inquiry procedure, four core group meetings were held with 26 undergraduate students who had completed the course on Semiology and Semiotics in Nursing, which is the course where the Nursing laboratory is most needed as a learning space. The analysis, based on a qualitative approach, had as fundamental theoretical support studies made by Friedlander and Hayashida, who deal with learning/teaching in the Nursing laboratory, and by authors who favor humanization in teaching such as, among others, Freire, Maturana, Morin, Assmann. Results point toward the relevance of the Nursing laboratory as a facilitator for the learning/teaching process. In their speech the students repeatedly state that the development of procedures in simulated situations enable them to become more self-assured and technically prepared for caring. In addition, they emphasize that feelings such as fear, lack of confidence, anxiety, anguish and panic become diminished at the time of their clinic experience when they have had previous learning in the laboratory. They have also acknowledged that some difficulties of structural nature have become obstacles to a high-quality learning development. In summary, in spite of the difficulties that have been pointed out by the students concerning the use of the Nursing laboratory in the learning/teaching process, they also recognize that this is the locus par excellence where they can develop their skills and appease their anxieties